Ethical particularism and moral universalism. Critical considerations on the conceptions of practical rationality and the "I" in Charles Taylor - Cortés Rodas, Francisco (Estudios de Filosofía, 1997)
They are considered in this article, first, the notion of Practical Rationality, the notion of Person, and the diagnosis of Modernity carried out by Charles Taylor's Sources of Self. The Making of the Modem ldentity. Second, and starting from the communicative view of Practical Rationalrty by Habermas, the author makes some critical notes to Taylor's posture trying to reveal so the problems arising from defining practical rationality from an ethical perspective.